A produção de textos médicos sobre a enfermidade amor hereos (séculos XI a XIV) - Silva, Natan Magalhães (2020)
This dissertation aims to investigate medical representations about the disease called amor hereos between the 11th and 14th centuries, a period of creation and development of General Studies in the regions of present-day France and Italy. The selected sources were: first the text translated from Arabic and adapted by Constantine, in the 11th century, Viaticum or Provisions for the Traveler and the Nourishment of the Settled (Viaticum pregrinantes); second, the medical comments attributed to the scholastic masters of Paris, Montpellier and, Siena about lovesickness in the Constantinian work: Gerard of Berry, Giles of Santarem and Peter os Spain (A and B) of the 13th century; finally, the Treaty of heroic love (Tractatus de amore heroico) of 1285, attributed to the catalan master and physicist Arnau de Vilanova, and the compendium, the Lily of medicine (Lilium Medicinae), 1306, by the master Bernard de Gordon, both from Montpellier. He sought to reconstruct in which conditions the knowledge about this disease reached the Latin West and how scholastic medicine received it. Assuming that the disease is a discursive construction, we will analyze how the representations about this disease were elaborated from the ancient and Arab medical tradition, especially through the works of Galen and Avicenna, and the discourses on courtly love present in vernacular literature and latin of the period,